Evaluation of intraocular pressure elevation after multiple injections of intravitreal ranibizumab - Yu, Alice L.; Seidensticker, Florian; Schaumberger, Markus; Welge-Lüssen, Ulrich-Christoph; Wolf, Armin (Clinical Ophthalmology, 2014)
We wanted to determine whether multiple injections of intravitreal ranibizumab was associated with an elevated intraocular pressure (IOP) in patients treated for neovascular age-related macular degeneration (AMD).This retrospective study examined 53 patients with neovascular AMD treated with multiple injections of intravitreal ranibizumab. The main outcome measure was the difference in IOP between the frequently-treated study eyes (>=15 injections) and the unfrequently-treated fellow control eyes (<= five injections). Patients were divided into three study groups: group I (35 patients with 15 to 19 injections); group II (15 patients with 20 to 29 injections); and group III (three patients with >=30 injections). The IOP was measured by Goldmann applanation tonometry 4 weeks after the last injection of intravitreal ranibizumab. For statistical analysis, the IOP was then correlated with the number of ranibizumab injections.Among the frequently-treated study eyes, the mean IOP was 13.68±2.91 mmHg (range, 8 to 20 mmHg). The unfrequently-treated fellow control eyes had a mean IOP of 13.45±3.09 mmHg (range, 9 to 25 mmHg). There was no significant correlation of the IOP difference between the study and control eyes with the number of ranibizumab injections (correlation coefficient 0.77; P=0.583). For each of groups I, II, and III, the difference in mean IOP between the study and control eyes was nonsignificant (P>0.05). There was also no significant association of the IOP difference between the study and control eyes with the number of ranibizumab injections for each group (P=0.391).Our study did not find an increased IOP in frequently-ranibizumab-treated eyes when compared to unfrequently-treated fellow control eyes. Further studies with a greater sample size are needed to evaluate whether an increased number of ranibizumab injections is associated with IOP changes.
EVALuna2:21197